The Box Crab Calappa hepatica as a Nuclear Species for the Opportunistic Foraging Behaviour of the Flowery Flounder, Bothus mancus, in the Indo-Pacific - Betti, Federico; Hoeksema, Bert W. (Diversity (Basel), 2024)
Some predatory fishes may exhibit opportunistic feeding behaviour by exploiting potential prey that is distracted, displaced, or exposed by the activities of a third party that acts as a ‘nuclear’ species. Other fishes mostly perform the role of ‘nuclear’ species, but benthic invertebrates, such as octopuses, have also been reported. Crabs are rarely observed in this role, with only a few records from the tropical Atlantic Ocean. Here, we report the temporary association between two specimens of the flowery flounder, Bothus mancus (family Bothidae), and a box crab, Calappa hepatica (family Calappidae), from the Philippines, representing the first record of a crab–fish feeding association in the Indo-Pacific region.